Negative Energy Balance Does Not Alter Fat-Free Mass During the Yukon Arctic Ultra—The Longest and the Coldest Ultramarathon - Schalt, Adriane; Johannsen, Michelle M.; Kim, Jimin; Chen, Richard; Murphy, Carl J.; Coker, Melynda S.; Gunga, Hanns-Christian; Coker, Robert H.; Steinach, Mathias (Frontiers in Physiology, 2018)
Purpose: The objective of this study was to determine alterations in caloric balance, body composition, metabolites, and cytokines in athletes participating in the Yukon Arctic Ultra. Methods: Ten participants traveling on foot in the 2017 692-km event were recruited for the study. Measurements and samples were obtained at pre-event, 278-km (C1), 384-km (C2), and post-event. Body composition measurements were obtained using bioelectrical impedance analysis. Accelerometer devices were utilized to provide an estimation of caloric expenditure and dietary recalls provided assessments of caloric intake. Blood serum samples were collected, processed, and analyzed using enzyme-linked immunosorbent assays or nuclear magnetic resonance. Results were analyzed using linear mixed model, presented as means±SD and considered significant at P<0.05. Results: Participants (37±10 yr; body mass index: 24.4±2.5 kg/m2; 8 males, 2 females) were recruited. Four males and one female completed the entire event in 260±19 hours. Caloric intake/expenditure was 4,126±1,115 kcal/day and 6,387±781 kcal/day, respectively, indicating a caloric deficit of 2,261±1,543 kcal/day. Total mass, body mass index, and fat mass were reduced at each time point of the event. Fat free mass was unchanged throughout the event. Follistatin was increased at C1 (1,715±876 pg/mL) in comparison to baseline. Acetoacetate increased significantly at post-event (6.1±1.5 mg/ml). Conclusions: Despite a pronounced caloric deficit and sustained activity under extreme cold conditions, fat free mass was preserved with an increase in serum follistatin and acetoacetate. Future studies should be directed at the role of nutrient strategies and/or training methods on the retention of fat free mass under these conditions.